An Analysis of Metaphors in Coldplay's A Head Full of Dreams Album - Ramadhan, Dhani Ringga; Wibowo, Hanafi (Program Studi Magister Linguistik Terapan UNJ, 2024)
This study analyzes metaphors in the song lyrics of Coldplay's album